Challange and Fighting Social Stigma in Patient With Schizophrenia in Indonesia. - Amar Akbar; Imam Zainuri; Lilik Ma'rifatul Azizah; Kyle Dornhofer (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2018)
Purpose - This article aims to give an opinion on the cause of still the case of pasung in Indonesia, physical restraint and reduction in people with mental illness (called pasung in indonesia), still found in indonesia, government program â€ indonesia free of pasungâ€ still can not erase indonesia from pasung. Design/methodology/approach -The approach to literature study causes the escape especially social stigma that occurs to make the case of the pipe still continues to exist Findings -The findings of many literature studies suggest that social stigma is a cause of social restraint in patients with severe psychiatric disorders Originality/value -The value of this study envolve Empowering people with mental disorders through social intervention can reduce the side effects of antipsychotic drugs and simultaneously help self-stigma in people with mental disorders